Impact of Saving Accounts’ Prizes on Customer Retention In Jordanian Commercial Banks Using SEM - Al-Nsour, Iyad (The Arab Journal of Administration, 2022)
This study aimed to find the impact of saving accounts prizes offered by commercial banks on customer retention, as well as to determine the statistical differences in customer retention according to age and sex. The study population consists of all saving accounts customers in the commercial banks in Jordan. There is no official information about the number of such customers. The pilot study results show that 17.9% of customers has saving accounts in commercial banks. The non-proportional clustered random sample was used. The sample calculations show that the required sample size is 235 customers. The researcher designed an electronic copy of the questionnaire on Google Drive. The city mall in Amman is the place of face-to-face distribution with targeted customers. For the purposes of this study, Smart PLS3 was used. Based on the results of the path analysis, it was found that there is a positive statistical impact of the saving accounts prizes on customer retention, and these prizes have a high power to explain the customer behavior towards the commercial banks in Jordan. The statistical differences show no statistically significant differences in the perceived saving accounts prizes and customer retention according to age and six. Finally, the study recommended more loyalty programs should be developed, more creativity in banking products based on financial immediate awards, and the national strategy should be developed to ensure that the awards are used for productive projects that are beneficial to the economy and create job opportunities, especially for young people and poor families.